The Evaluation of Injures Caused by Falling According to Forensic Medicine - Tokdemir, Mehmet; Türkoğlu, Abdurrahim; Kafadar, Hüseyin; Deveci, Süleyman Erhan (The Bulletin of Legal Medicine, 2007)
Falls are one of the leading causes of admission to emergency and deaths. There is more than one classification of the falls. In this study we classified falls according to height of the falls: High level (>5 meters) and low level (
Keywords: falling; height; life threatening; glasgow coma score